ANALYSIS ON RECENT BULOG’S ASSIGNMENTS FOR BOTH PRODUCER AND CONSUMER OF RICE IN INDONESIA - Kuntoro Boga Andri (UNEJ e-Proceeding, 2012)
The objectives of this study are: 1) to review the assignments of BULOG in the recent time, 2) to understand impact of the recent BULOG policies toward consumers and farmers. This study showed that BULOG functions are weakening by the liberalization, and market share becomes smaller time by time. RASKIN program, national stock and domestic rice procurement are the government instrument by BULOG to protect consumer’s wealth, farmers’ income guaranty and national food security. BULOG policy also aimed to give protection to farmer and consumers and to give a guarantee in rice distribution for poor groups. Regarding farmers’ observation, major problems on rice agribusiness is marketing aspect especially low and fluctuated price. Most of them expect government good policies to develop farming and to increasing income. Yet, BULOG 1 function as a market regulator is still required.